The mutagenic hazards of polycyclic aromatic hydrocarbons (PAHs) in settled house dust - Maertens, Rebecca (University of Ottawa (Canada), 2005)
Settled house dust (SHD) may be a significant source of children's indoor exposure to hazardous substances including polycyclic aromatic hydrocarbons (PAHs). In this study, the extent to which mutagenic PAHs are present in SHD was examined, and the overall mutagenic hazards of SHD were evaluated using the Salmonella Mutagenicity Test. The results indicate a predominance of frameshift mutagens in the SHD, and a significant positive correlation was identified between mutagenicity and PAH concentration. Mutagenicity was empirically related to several household attributes including vacuuming habits and the number of inhabitants in the home. There is some indication that PAH concentration in SHD is related to an urban home location and the presence of smokers, but the effects are weak. A risk assessment to evaluate the excess lifetime cancer risks posed by preschoolers' non-dietary ingestion of PAHs in SHD revealed that such exposures may result in risks that exceed 1 x 10-5.
Keywords: Biology, Microbiology.; Health Sciences, Public Health.; Environmental Sciences.